(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a systematic analysis of the semantic features of phraseological units in the Uzbek language, including their semantic structure, polysemy, imagery, expressiveness, and national-cultural components. The study highlights the differences between phraseological units and lexical items, as well as their contextual semantic variations and functional roles in speech.